Volcanism in Latin America: Advances in the region from the First ALVO Congress. (October 2022) - Agusto, Mariano; Forte, Pablo; Aguilera, Felipe; Arciniega Ceballos, María Alejandra
Abstract: The Latin American Association of Volcanology (ALVO) arose in 2010 as a regional network, promoting regional cooperation, the exchange of experiences and the strengthening of local capacities in the field of volcanology. In 2020, ALVO organized its first scientific congress under the slogan 'Volcanology in and for Latin America' ( 1er Congreso ALVO: Volcanología en y para Latinoamérica ). The Special Issue, Volcanism in Latin America, hosts several works presented at this Congress. The articles that constitute this Special Issue cover a broad spectrum of topics studied by many research groups and institutions working on volcanology in the region. Such topics include disciplines like physical volcanology, geochemistry, seismology, remote sensing, volcano observatories, instrumentation, and volcanic hazards and risks, among others. These papers represent good examples of the state-of-the-art of volcanology research in Latin America. Highlights: Update on the state of volcanology in Latin America. Volcanism in Latin America, from the mantle to the atmosphere. Volcanic observatories, monitoring and instrumentation. Volcanic hazards assessment. Volcanic risks: relation between volcanism and society.